2019
DOI: 10.1108/nfs-09-2018-0263
|View full text |Cite
|
Sign up to set email alerts
|

Consumer knowledge and attitudes toward functional foods in Lebanon

Abstract: Purpose The development and commerce of functional foods (FF) is complex, expensive and risky. Besides technological obstacles and legislative aspects, consumer demands also need to be considered. The purpose of this study is to assess the Lebanese consumer’s knowledge, attitudes and acceptance of FF and functional ingredients. Design/methodology/approach A cross-sectional study recruited a convenience sample of adults living in Mount Lebanon in 2015. An interviewer-based questionnaire assessed socio-demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 39 publications
(54 reference statements)
4
20
0
Order By: Relevance
“…In summary, the findings of the cross-cultural comparative studies indicate that there are cultural differences between American and European consumers, and between different European countries regarding functional foods behaviour. Foods studies conducted in the emerging countries context showed results in accordance with Western functional foods studies when it comes to the effect of some socio-demographic (gender, age, education) (Ares et al , 2010; Bilgiç and Yüksel, 2012) or some drivers, such as health motivation (Ares et al , 2008; Chammas, 2019). However, differences were found in functional foods social representations.…”
Section: Functional Foods Choice Literaturesupporting
confidence: 59%
See 3 more Smart Citations
“…In summary, the findings of the cross-cultural comparative studies indicate that there are cultural differences between American and European consumers, and between different European countries regarding functional foods behaviour. Foods studies conducted in the emerging countries context showed results in accordance with Western functional foods studies when it comes to the effect of some socio-demographic (gender, age, education) (Ares et al , 2010; Bilgiç and Yüksel, 2012) or some drivers, such as health motivation (Ares et al , 2008; Chammas, 2019). However, differences were found in functional foods social representations.…”
Section: Functional Foods Choice Literaturesupporting
confidence: 59%
“…Most of the studies on functional foods are focused on developed Western countries, mainly in North America and Europe, leaving out potential emerging markets. Only a few studies, on functional foods acceptance, have been conducted in emerging countries: Ares et al (2008, 2010, Uruguay); Schnettler and Grunert (2016, Chile); Bilgiç and Yüksel (2012) and Gok and Ulu (2019, Turkey); Siegrist et al (2015, China); de Dienes et al (2011, Venezuela); Hassan, (2011a, 2011b) and Salleh et al (2015, Malaysia); and Chammas et al (2019, Lebanon – MENA region).…”
Section: Functional Foods Choice Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Probably any natural, beneficial compounds for both therapy and health, they involved dietary fibers, polyphenols, antioxidants, spices, flavonoids, vitamins, probiotics, and polyunsaturated fatty acids [ 17 ]. Believing that functional components will assist in the prevention of diseases leads to a positive attitude towards free fatty acid [ 18 ].…”
Section: Nutraceuticalsmentioning
confidence: 99%